Proceedings of the North American Society of Head and Neck Pathology, Los Angeles, CA, March 20, 2022: SWI/SNF-deficient Sinonasal Neoplasms: An Overview - Agaimy, Abbas (Head and Neck Pathology, 2022)
The pathology of poorly differentiated sinonasal malignancies has been the subject of extensive studies during the last decade, which resulted into significant developments in the definitions and histo-/pathogenetic classification of several entities included in the historical spectrum of “sinonasal undifferentiated carcinomas (SNUC)” and poorly differentiated unclassified carcinomas. In particular, genetic defects leading to inactivation of different protein subunits in the SWI/SNF chromatin remodeling complex have continuously emerged as the major (frequently the only) genetic player driving different types of sinonasal carcinomas. The latter display distinctive demographic, phenotypic and genotypic characteristics. To date, four different SWI/SNF-driven sinonasal tumor types have been recognized: SMARCB1(INI1)-deficient carcinoma (showing frequently non-descript basaloid, and less frequently eosinophilic, oncocytoid or rhabdoid undifferentiated morphology), SMARCB1-deficient adenocarcinomas (showing variable gland formation or yolk sac-like morphology), SMARCA4-deficient carcinoma (lacking any differentiation markers and variably overlapping with large cell neuroendocrine carcinoma and SNUC), and lastly, SMARCA4-deficient sinonasal teratocarcinosarcoma. These different tumor types display highly variable immunophenotypes with SMARCB1-deficient carcinomas showing variable squamous immunophenotype, while their SMARCA4-related counterparts lack such features altogether. While sharing same genetic defect, convincing evidence is still lacking that SMARCA4-deficient carcinoma and SMARCA4-deficient teratocracinosarcoma might belong to the spectrum of same entity. Available molecular studies revealed no additional drivers in these entities, confirming the central role of SWI/SNF deficiency as the sole driver genetic event in these aggressive malignancies. Notably, all studied cases lacked oncogenic IDH2 mutations characteristic of genuine SNUC. Identification and precise classification of these entities and separating them from SNUC, NUT carcinoma and other poorly differentiated neoplasms of epithelial melanocytic, hematolymphoid or mesenchymal origin is mandatory for appropriate prognostication and tailored therapies. Moreover, drugs targeting the SWI/SNF vulnerabilities are emerging in clinical trials.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Epithelioid sarcoma; Head and neck; Rhabdoid tumor; SMARCB1; SWI/SNF complex; Teratocarcinosarcoma